Dialogue for improved internationalization of higher education - Aw, Fanta, Egron Polak, Eva; (Revista Educación Superior y Sociedad (ESS), 2019)
The article provides a brief summary of the context, the rationales and the goals that led several international higher education associations and networks from around the world to hold two special events on higher education internationalization. It summarizes the two Global Dialogues that have been organized, explaining who the main actors were, what were the topics covered in each event and what outcomes each of them brought. Though successful in identifying some of the key issues the various stakeholders need to keep in mind as internationalization continues to evolve and expand, the Dialogues also faced serious obstacles in their fundamental effort of bringing ALL voices to the table. These obstacles are outlined as well and are noted even as the 3rd dialogue is announced and will most likely take place in Brazil in the future.